Elevation of serum soluble intercellular adhesion molecule-1 (sICAM-1) and sE-selectin levels in bronchial asthma. - Kobayashi, T (1994)
Adhesion molecules such as ICAM-1 and E-selectin have been shown to play important roles in the production of allergic inflammation. In the present study, we measured serum soluble ICAM-1 (sICAM-1) and soluble E-selectin (sE-selectin) levels by ELISA in 42 patients with bronchial asthma (22 atopic and 20 non-atopic) during asthma attacks and in stable conditions in order to assess the state of ICAM-1 and E-selectin in allergic inflammation. Both serum sICAM-1 levels and serum sE-selectin levels in sera obtained during bronchial asthma attacks were higher than those in sera obtained in stable conditions. These findings were observed regardless of atopic status. To examine the regulatory mechanism in the elevation of serum sICAM-1 and sE-selectin levels, serum tumour necrosis factor-alpha (TNF-alpha) levels were measured by ELISA. TNF-alpha levels in sera obtained during bronchial asthma attacks were higher than those in sera obtained in stable conditions. There was a correlation between the nature of change in serum TNF-alpha levels and the nature of change in serum sICAM-1 levels or serum sE-selectin levels, though serum TNF-alpha levels did not correlate with serum sICAM-1 levels or serum sE-selectin levels. These results suggest that higher levels of sICAM-1 and sE-selectin during asthma attacks may reflect the up-regulation of ICAM-1 and E-selectin expression in allergic inflammation, and that the soluble form of these adhesion molecules may be useful markers for the presence of allergic inflammation. TNF-alpha is shown to enhance the expression and release of ICAM-1 and E-selectin in vitro, however; the regulatory mechanism in the elevation of serum sICAM-1 and sE-selectin levels remains to be clarified.